Coreoedição: fluxo criativo na videodança - Silva, Adriano André Rosa da (2021)
This dissertation discusses image creation through choreoediting, aiming to reflect through techniques and creative processes in videodance ways of recording and editing images. It presents an artistic-teaching path, through experiences between dance and cinema, dialoguing with authors of the montage, such as Sergei Eisenstein (2002), Andrei Tarkovsky (1998) and Maya Deren (1960). It discusses theories such as the dialectic of Soviet cinema montage, the sequence plan and the poetics of the elements expressed in the film scene and how these can be used as a form of transition during the editing of a video or film. The concepts discussed here show the ways in which I developed this research that expanded his poetics through the artistic residency “Coreoedition: creative flow in videodance”, developed by Cena Universidade (UFPE - Federal University of Pernambuco). This dissertation also reflects on the conscious and kinesthetic relationships of the choreoediting process, as the act of choreoediting is a bodily choreographic process. Finally, it points out videodance and choreoediting as an artistic possibility that can be experienced by many artists, whether from the audiovisual or the performing arts, because in the process of this research, the singularity of the body that expresses itself in videodancing was identified, creating poetics through of moving images using cameras, computer software and cell phone applications.